The effects of strength, plyometric and combined training on strength, power and speed characteristics in high-level, highly trained male youth soccer players: a systematic review and meta-analysis - Oliver, J. L.; Ramachandran, A. K.; Singh, U.; Ramirez-Campillo, R.; Lloyd, R. S. (Sports Medicine, 2024)
Key Points: